Critical State Line, Roscoe Dan Hvorslev Surface : Studi Kasus Sampel Tanah U.K. Maranatha Bandung - Nugraha, Andrias Suhendra (Jurnal Teknik Sipil, 2005)
Stability is one of the regular calculation elements in geotechnical engineering. Stability calculations relate to the collapse of a soil mass with large deformation occurring in the collapse plane followed by the collapse of the geotechnical structure. This shows that the analysis of stress-strain behavior at critical state is very important. Soil behavior depends not only on the initial and final stress state but also on the trajectory at which the stress and strain state changes and the previous loading history. The trajectory is different for each type and consolidation state of the soil sample. However, the trajectory will tend towards a unique boundary surface and then along the surface to a single and unique critical state line. This paper aims to describe the critical state line, which is the final destination of the collapse of the loaded soil, and to describe a boundary surface consisting of the Roscoe surface, which is typically traversed by normally consolidated soil samples, and the Hvorslev surface, which is typically traversed by overconsolidated soil samples. A case study was conducted on clay soil samples at U.K. Maranatha Bandung. The shear test conducted was undrained sriaxial consolidated test. The case study shows that the soil sample belongs to normally consolidated clay. The critical state parameters obtained are M and 2.